The academic‐practice gap: Strategies for an enduring problem. Issue 1 (16th August 2017) - Huston, C.L.; Phillips, B.; Jeffries, P.; Todero, C.; Rich, J.; Knecht, P.; Sommer, S.; Lewis, M.P.
Abstract: The academic‐practice gap in nursing is well documented. Academe is criticized for producing nurses insufficiently prepared to fully participate in patient care. Practice settings are criticized for having unrealistic expectations of new graduates. This article is based on a review of the literature and an exploration of contemporary practices used to bridge academic and practice partnerships. Differences in outcome expectations for new graduates between academe and practice are outlined and consequences of the gap for new graduates, patients, and employers are discussed. Five specific strategies to address the gap are discussed, with the primary realm and responsibility for two falling to education, one to practice, and two to both. Strategies discussed include increased use of simulated learning in nursing education; disruptive innovations in education that promote learner‐centered active learning; extended orientation/Transition to Practice Programs for new graduates; dedicated education units; and academic service partnerships. Current literature suggests the viewpoints of academic and practice leaders continue to appear divergent. Closing the gap will require a dedicated and coordinated response from both academe and clinical practice.